REDISCOVERY OF CHEILOTHECA MALAYANA AND THE IDENTITY OF CHEILOTHECA, ANDRESIA AND MONOTROPASTRUM (ERICACEAE-MONOTROPOTDEAE) - HSUAN KENG (REINWARDTIA, 1974)
Andreeia, Monotropastrium and Wirtge-nia are reduced to the synonymy of Ckeilotheca. Four species are accepted, keyed out ami enumerated; a new combination, Ckeitotheen huiailie (D. Don) H. Keng, and a new species, Chtiilothtfcti aleumertima  H. Rene, are proposed.